2006
DOI: 10.1042/bj20051143
|View full text |Cite
|
Sign up to set email alerts
|

Metallothionein protects against oxidative stress-induced lysosomal destabilization

Abstract: The introduction of apo-ferritin or the iron chelator DFO (desferrioxamine) conjugated to starch into the lysosomal compartment protects cells against oxidative stress, lysosomal rupture and ensuing apoptosis/necrosis by binding intralysosomal redox-active iron, thus preventing Fenton-type reactions and ensuing peroxidation of lysosomal membranes. Because up-regulation of MTs (metallothioneins) also generates enhanced cellular resistance to oxidative stress, including X-irradiation, and MTs were found to be ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
136
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(151 citation statements)
references
References 52 publications
11
136
0
4
Order By: Relevance
“…MTs are a class of low-abundance cytoplasmic SH-rich proteins binding a variety of metals, iron included, 30 whose upregulation is highly protective against a number of harmful conditions, in particular those in which oxidative stress is involved. 29,[53][54][55][56][57] These proteins are often overexpressed in various cancers, making them more resistant to irradiation and drugs that induce oxidative stress. 58 In the present work, MT1A and MT2A were found poorly expressed in HTC cells under basal conditions, but were easily upregulated by ZnCl 2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MTs are a class of low-abundance cytoplasmic SH-rich proteins binding a variety of metals, iron included, 30 whose upregulation is highly protective against a number of harmful conditions, in particular those in which oxidative stress is involved. 29,[53][54][55][56][57] These proteins are often overexpressed in various cancers, making them more resistant to irradiation and drugs that induce oxidative stress. 58 In the present work, MT1A and MT2A were found poorly expressed in HTC cells under basal conditions, but were easily upregulated by ZnCl 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Since MT upregulation has been reported to protect against LMP induced by various kinds of oxidative stress, 29 we focused on this group of proteins, which bind a variety of metals, including iron (for a review see ref. 30 ) and, particularly, on the inducible MT1A and MT2A isoforms.…”
Section: Effect Of Mt (Metallothionein) Autophagy On Tnf and Chx Toximentioning
confidence: 99%
“…The cytosol contains a range of iron-binding proteins, such as metallothioneins, Hsp70 and ferritin (Baird et al, 2006, Kurz and Brunk, 2009, Kurz et al, 2011. These can all be autophagocytosed and then are able to bind lysosomal redox-active iron for a limited period of time until they are degraded.…”
Section: The Role Of Lysosomes In Intracellular Iron Metabolismmentioning
confidence: 99%
“…Templeton and Cherian (1991) found that the Gradually, the facts that MTs are involved in the homeostatic regulation of metals which provides a reservoir of metals for other metalloproteins or metalloenzymes, in heavy metal detoxification, in protection of tissues against various forms of oxidative injuries and transferring of essential metals (Coyle et al, 2002;Baird et al, 2006) (Figure 1). All the phenomena could be elucidated by chemical property of the thiolate bond (Suzuki et al, 2002).…”
Section: Structure Characteristics Of Mtsmentioning
confidence: 99%